Anti‐phosphatidylserine/prothrombin complex antibodies in patients with cutaneous vasculitis: Possible involvement in the pathogenesis. Issue 5 (18th February 2021) - Kawakami, Tamihiro; Tamura, Yuto; Dong, Yupeng; Yoshinari, Miku; Nishibata, Yuka; Masuda, Sakiko; Tomaru, Utano; Ishizu, Akihiro
Abstract: We assessed the IgG and IgM prevalence of anti‐phosphatidylserine/prothrombin complex (aPS/PT) antibodies (Abs) in patients with vasculitis using a novel commercial ELISA kit. To examine whether aPS/PT Abs were involved in the pathogenesis of cutaneous vasculitis, inbred wild‐type rats were intravenously administered with a rat IgM class aPS/PT monoclonal Ab established previously or with rat immunoglobulins as controls. To express PS on the surface of vascular endothelium, these rats were given a subcutaneous injection of cell‐free histones in advance. Serum IgM aPS/PT Ab levels were elevated in patients with systemic vasculitis with skin involvement and cutaneous arteritis compared to those in patients with systemic vasculitis without skin involvement and healthy controls. There was no significant difference in the serum levels of IgG aPS/PT Abs between the patients and healthy controls. Correspondingly, inbred wild‐type rats intravenously administered with the aPS/PT monoclonal IgM Ab after appropriate priming‐subcutaneous histone injection developed cutaneous vasculitis. Some rats given rat IgM instead of the aPS/PT monoclonal Ab also developed cutaneous vasculitis, whereas vasculitis did not occur in rats given IgG or only priming by histones. We suggested that IgM aPS/PT Abs could be involved in the pathogenesis of cutaneous vasculitis based on these findings.